(untitled) (International relations and international law Journal, 2016)
In this article the activities and the role of the Interparliamentary Assembly of the CIS Member States in the process of integration convergence of the states, in the removal of obstacles and barriers to free trade are examined. Particular attention is paid to the mechanism of unification and harmonization of legislation of CIS countries legislation, as the main direction of the activities of the IPA. Based on the analysis of instruments of international law, the peculiarities of the legal status of the IPA CIS as of interstate body were identified, the role of model laws (for example the Model Commercial Code and the Model Customs Code) in unification of the legislation was investigated). The author concluded that in the regulations of the IPA CIS terms «convergence» and «unification» are used as synonyms, and there is no distinction between them. The term «harmonization» is not used in these documents are at all